2008
DOI: 10.1007/s00436-008-1066-5
|View full text |Cite
|
Sign up to set email alerts
|

The key steroidogenic enzyme 3β-hydroxysteroid dehydrogenase in Taenia solium and Taenia crassiceps (WFU)

Abstract: Larval and adult stages of Taenia solium and Taenia crassiceps WFU strain were analyzed by histochemical and biochemical methods to determine the existence of steroid pathways. The presence of the key enzyme 3beta-hydroxisteroid-dehydrogenase (3beta-HSD) was examined in frozen sections of cysticerci obtained from mice and segments of tapeworms obtained from the intestine of hamsters. 3beta-HSD activity was detected by nitroblue-tetrazolium products after incubation with dehydroepiandrosterone, androstendiol, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Present data confirm our previous results that showed the ability of T. crassiceps WFU infrapopulations to transform [ 3 H]DHEA to androgens, such as testosterone and androstenediol, and the oestrogen 17b-oestradiol Valdéz et al, 2006;Fernández Presas et al, 2008). Results shown here indicate that cysticerci that have proliferated for several months in the abdominal cavity of mice, maintain their steroidogenic capacity.…”
Section: Discussionsupporting
confidence: 92%
“…Present data confirm our previous results that showed the ability of T. crassiceps WFU infrapopulations to transform [ 3 H]DHEA to androgens, such as testosterone and androstenediol, and the oestrogen 17b-oestradiol Valdéz et al, 2006;Fernández Presas et al, 2008). Results shown here indicate that cysticerci that have proliferated for several months in the abdominal cavity of mice, maintain their steroidogenic capacity.…”
Section: Discussionsupporting
confidence: 92%
“…We have also demonstrated that T. solium cysticerci synthesized androgens and small quantities of estrogens in vitro [34]. Recent results from our laboratory also showed that T. solium and T. crassiceps cysticerci as well as the adult worms synthesized steroid hormones from tritiated progesterone and dehydroepiandrosterone [35,43]. These results strongly suggest the presence and activity of steroidogenic enzymes in cysticerci.…”
Section: Introductionsupporting
confidence: 61%
“…To this regards, our group has recently reported the transformation of DHEA to androgens in Taenia solium and Taenia crassiceps cysticerci [35]. Furthermore, a recent paper from our group has demonstrated the presence and activity of 3␤-hydroxysteroid dehydrogenase/delta 5-4 in T. crassiceps WFU and T. solium adult worms and cysticerci [43]. Interestingly, immunoreactivity for 3␤-hydroxysteroid dehydrogenase/delta 5-4 has been shown in the cytoplasm of the parasite Sarcocystis spp.…”
Section: Discussionmentioning
confidence: 84%
“…However, the presence of a respective receptor in these organisms implies that they might also express cognate ligands, which subsequently could bind to members of the TNF-receptor family on host cells (such as DC), thus triggering apoptosis. Apart from components of the TNF signaling machinery, it has recently also been demonstrated that cestode larvae ( T. crassiceps cysticerci) are capable of producing steroid hormones [57]. Although in this system only the production of sex steroids has been tested, it is conceivable that they also produce glucocorticoids which might, either together with TNF-ligands or as an alternative, be involved in triggering host DC apoptosis.…”
Section: Discussionmentioning
confidence: 99%